Temporal Analysis of Land Surface Temperature for Urban Heat Island Detection in Thimphu, Bhutan - Samdrup, Yeshey (2024)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies